Feeling Normal : Sexuality and Media Criticism in the Digital Age - Griffin, F. Hollis (Book collections on Project MUSE., 2017)
The explosion of cable networks, cinema distributors, and mobile media companies explicitly designed for sexual minorities in the contemporary moment has made media culture a major factor in what it feels like to be a queer person. F. Hollis Griffin demonstrates how cities offer a way of thinking about that phenomenon. By examining urban centers in tandem with advertiser-supported newspapers, New Queer Cinema and B-movies, queer-targeted television, and mobile apps, Griffin illustrates how new forms of LGBT media are less "new" than we often believe. He connects cities and LGBT media through the experiences they can make available to people, which Griffin articulates as feelings, emotions, and affects. He illuminates how the limitations of these experiences--while not universally accessible, nor necessarily empowering--are often the very reasons why people find them compelling and desirable.